PENERAPAN STRATEGI REACT TERHADAP PENINGKATAN AKTIVITAS SISWA SMK NEGERI 1 PAINAN - Titi Sumarni (Ensiklopedia Social Review, 2020)
As mathematic teacher, we should be able to create an interesting and active learning, beside that she should be able to create a good competition in the class. It has positive effect to gain optimum study result. Teacher should use variation method and learning strategy in learning so that teaching and learning become easy and fun for the student. The student will be more active and have motivation to study. The implementation of REACT strategy for student of XI TKJ SMK Negeri 1 Painan is suitable to improve students activity in learning. The research is classroom action research which consist of two cycles, each cycles involve four stages : (1) planning, (2) acting, (3) observing, and (4) reflecting. The sample of the research are 34 student. The data is collected by using observation paper. The analysis of data is done by using descriptive qualitative. The result of the students activity in asking question in cycle I is 43% and in cycle II is 54%. It means that the activity in asking question achieve avarage level. The activity in giving sugestion or giving opinion also get on avarage level in cycle 1 is 28% and in cycle II is 43%. The activity in group discussing get high level.It happened in cycle I anda cycle II .They have same percentage. It is 67% .